The Potential of EMSA Eritin to Modulate T Cells (CD4+ and CD8+) in Balb/C Mice Model of Diabetes Mellitus - Rohie, Ade MC; Rifa'i, Muhaimin (Graduate School, Universitas Brawijaya, 2015)
EMSA Eritin is a medicinal polyherbal contains with soy bean, coconut water and red rice extract. In several studies of this individual components have proven the potential to modulate lymphocyte cells that indirectly lowering blood glucose levels in diabetes meliitus. This study was aimed to analyzing the effect of polyherbal EMSA Eritin on the expression of CD4+, CD8+ and SDF-1 cells population in mice model of diabetes mellitus. Neonatal d-5 mice was intraperitoneally injected with Streptozotocin (STZ) 100 mg.kg-1 BW. Four weeks post injection the mice was treated with EMSA Eritin in three doses 0.3125 mg.g-1 BW, 3.125 mg.g-1 BW and 31.25 mg.g-1 BW for 14 days. Cells Profile of T lymphocyte (CD4+ and CD8+) and chemokine SDF-1 were analyzed by Flow cytometry. Data were analyzed with One-way ANOVA (p<0.05) and Duncan test using SPSS 16.0 for Windows. The result showed that EMSA Eritin significantly increased T lymphocyte (CD4+ and CD8+) in optimum dose 3.125 mg.g-1 BW and suppress SDF-1 production in high dose (31.25 mg.g-1 BW) as well as the blood glucose level measurement. This study suggest that polyherbal EMSA Eritin has a potential to decreased blood glucose level in mice model of diabetes mellitus.Keywords: CD4+, CD8+, diabetes mellitus, EMSA Eritin, SDF-1